A Multidimensional Perspective on Language Planning and Policy in Singapore: Theory, Practice and Challenges - Zheng, Xianlang; Luo, Na (Journal of Current Social Issues Studies, 2025)
As a model of a multilingual country, Singapore's language policy has always aimed to balance linguistic diversity and social integration. Through the synergy of status planning, corpus planning, prestige planning and education planning, Singapore has successfully shaped a multilingual society with English as the lingua franca while preserving the cultural identity of the community. However, the new challenges posed by globalization and intergenerational linguistic change have prompted Singapore to continuously adjust its policy framework. Taking Singapore as an example, this paper explores the practical paths, effectiveness and inherent tensions of its language policy from the definitions of language planning and language policy, as well as from the perspectives of functionalism, social constructivism and critical theory.
Keywords: Singapore; language planning; language policy; language prestige; international cases